2013
DOI: 10.1589/jpts.25.977
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Posterior Oblique Sling Activity during Hip Extension in the Prone Position on the Floor and on a Round Foam Roll

Abstract: [Purpose] The aim of this study was to compare muscle activity of the posterior oblique sling during prone hip extension (PHE) on the floor and on a round foam roll. [Subjects] Twenty-two (11 male, 11 female) healthy volunteers were recruited for this study. [Methods] The participants performed PHE on the floor and on a round foam roll. Surface electromyography (EMG) was recorded from the contralateral latissimus dorsi (LD), contralateral erector spinae (ES), ipsilateral ES, ipsilateral gluteus maximus (GM), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
(25 reference statements)
0
11
1
Order By: Relevance
“…Furthermore, Kim et al [3] showed significant improvement in the contralateral latissimus dorsi, the ipsilateral erector spinae, and gluteus maximus activities when these were measured by POSM activation on an unstable support and when compared with that in a stable support. This suggests that the thoracolumbar fascia significantly contributes to the stability of the hip and pelvis, which is similar to the results of this study.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Kim et al [3] showed significant improvement in the contralateral latissimus dorsi, the ipsilateral erector spinae, and gluteus maximus activities when these were measured by POSM activation on an unstable support and when compared with that in a stable support. This suggests that the thoracolumbar fascia significantly contributes to the stability of the hip and pelvis, which is similar to the results of this study.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Vleeming et al [10] also suggested the combined action of the POSMs for stabilizing the lumbopelvic joint. For simultaneous activation of the POSMs, several researchers have suggested prone hip extension (PHE) exercise [2,3,11,12]. However, there are only a few studies on increasing POSM activation during PHE according to the activation of the latissimus dorsi, which is broadly covered by the thoracolumbar fascia among the POSMs.…”
mentioning
confidence: 99%
“…Because the gluteus maximus (GM) muscle fibers are aligned perpendicular to the sacroiliac joint, GM contractions compress the sacroiliac joint, and contribute to pelvic stability 1 ) . GM contraction also contributes to the transmission of force from the lower extremity to the pelvis through the sacroiliac joint during functional activities, such as ambulation 2 , 3 , 4 ) . Bruno et al 5 ) reported that patients with low back pain have a significantly delayed onset of GM activity when performing prone hip extension movements compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are various kind of exercises to activate PMC (11)(12)(13). Conventional exercise of the trunk extensors (CETE) is a way to increase the muscle activity of PMC and generally is performed as over ground exercises on a mat.…”
Section: Introductionmentioning
confidence: 99%